2006
DOI: 10.1111/j.1462-5822.2005.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-linked kinase is an essential link between integrins and uptake of bacterial pathogens by epithelial cells

Abstract: SummaryEntry of Streptococcus pyogenes or group A streptococcus (GAS) into host cells is mediated by fibronectin bound to surface proteins, M1 or PrtF1, forming a bridge to α α α α 5 β β β β 1 integrins. This interaction leads to cytoskeletal rearrangement and uptake of streptococci. We postulated that integrin-linked kinase (ILK), which directly associates with integrins, is the universal link between integrins and several bacterial pathogens. We showed that inhibition of ILK expression by siRNA silencing, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 44 publications
1
77
0
Order By: Relevance
“…In this context, it is notable that mRNA of the ILK was up-regulated in infected HBMEC in response to both meningococcal isolates. ILK was recently described to act as an essential link between integrins and the uptake of group A streptococci into epithelial cells (63). In the present study, it now becomes evident that there is also increased transcriptional activity of negative regulators of the MAPK signaling pathways.…”
Section: Discussionsupporting
confidence: 61%
“…In this context, it is notable that mRNA of the ILK was up-regulated in infected HBMEC in response to both meningococcal isolates. ILK was recently described to act as an essential link between integrins and the uptake of group A streptococci into epithelial cells (63). In the present study, it now becomes evident that there is also increased transcriptional activity of negative regulators of the MAPK signaling pathways.…”
Section: Discussionsupporting
confidence: 61%
“…The prtF1 gene was introduced into strain M1 Ϫ 90-226 to generate a M1 Ϫ PrtF1 ϩ recombinant of strain 90-226. This recombinant regained the potential to invade epithelial cells efficiently in the presence of exogenous Fn (10). Invasion assays showed that expression of PrtF1 protein by strain M1 Ϫ 90-226 resulted in greater uptake of bacteria by TGF-␤1-treated epithelial cells without an exogenous source of Fn (Fig.…”
Section: Tgf-␤1 Enhanced Invasion Depends On Fn-binding Proteins Of Gasmentioning
confidence: 99%
“…Our previous findings demonstrated that inactivation of integrin signaling signif-icantly inhibited GAS invasion (10,12). TGF-␤1 is known to up-regulate integrin signaling and expression of ECM proteins; therefore, we postulated that TGF-␤1 could enhance GAS invasion.…”
Section: Tgf-␤1 Enhances Gas Invasion Of Epithelial Cellsmentioning
confidence: 99%
See 2 more Smart Citations